7‐Epitaxol induces apoptosis in cisplatin‐resistant head and neck squamous cell carcinoma via suppression of AKT and MAPK signalling. Issue 23 (29th October 2022) - Yang, Hui‐Ju; Velmurugan, Bharath Kumar; Chen, Mu‐Kuan; Lin, Chia‐Chieh; Lo, Yu‐Sheng; Chuang, Yi‐Ching; Ho, Hsin‐Yu; Hsieh, Ming‐Ju; Ko, Jiunn‐Liang
Abstract: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide. Although cisplatin‐based chemotherapy is commonly used in HNSCC, frequent development of cisplatin resistance is a potential cause of poor HNSCC prognosis. In the present study, we investigated the anticancer efficacy of a major paclitaxel metabolite namely 7‐Epitaxol in cisplatin‐resistant HNSCC. The findings revealed that 7‐Epitaxol exerts cytotoxic effects in cisplatin‐resistant HNSCC cell lines by inducing cell cycle arrest and intrinsic and extrinsic apoptotic pathways. Specifically, 7‐Epitaxol increased Fas, TNF‐R1, DR5, DcR3 and DcR2 expressions, reduced Bcl‐2 and Bcl‐XL (anti‐apoptotic proteins) expressions, and increased Bid and Bim L/S (pre‐apoptotic proteins) expressions, leading to activation of caspase‐mediated cancer cell apoptosis. At the upstream cell signalling level, 7‐Epitaxol reduced the phosphorylation of AKT, ERK1/2 and p38 to trigger apoptosis. In vivo results showed that animals treated with 7‐Epitaxol show antitumor growth compared to control animals. Taken together, the study demonstrates the potential anticancer efficacy of 7‐Epitaxol in inducing apoptosis of cisplatin‐resistant HNSCC cells through the suppression of AKT and MAPK signalling pathways.